Economics: study guide - Atkinson, Brian (Harlow, England: Addison-Wesley Educational Publishers Inc, 2000)
This book is an invaluable aid to learning introductory level undergraduate and A-level economics.
lje 5/9/13
Loans
Keywords: Economics